2017
DOI: 10.1515/jtim-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive clinical predictors of portal hypertensive gastropathy in patients with liver cirrhosis

Abstract: PSR is better predictor of PHG than RLAR but at the expense of relatively lower specificities and NPV likely because of underlying pathophysiology (portal hypertension) which is similar for esophageal varices, PHG, and ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 14 publications
7
15
0
Order By: Relevance
“…In our study there were 122 (76.25%) patients with esophageal varices, similar results were found in studies from Egypt, Serbia, India, and Pakistan. 15,19-21 Whereas a cross-sectional study from Lahore, Pakistan by Khan and colleagues 22 showed only a 22.3% of patients with esophageal varices. Another study conducted on 197 patients from Peshawar showed esophageal varices in 32% of the patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study there were 122 (76.25%) patients with esophageal varices, similar results were found in studies from Egypt, Serbia, India, and Pakistan. 15,19-21 Whereas a cross-sectional study from Lahore, Pakistan by Khan and colleagues 22 showed only a 22.3% of patients with esophageal varices. Another study conducted on 197 patients from Peshawar showed esophageal varices in 32% of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, a cut-off value of 4.42 was taken, while according to the Child-Turcotte-Pugh grades we observed 67 (41.88%) patients with grade A, followed by 61 (38.12%) patients with grade B, and 32 (20%) patients with grade C, which is consistent with the findings reported in previous studies. 19,21 A Serbian study by Alempijevic et.al. 19 showed that 24.5% of the patients with no esophageal varices were identified by upper GI endoscopy, 22.3% had grade I esophageal varices, 33% had grade II esophageal varices, 16% had grade III esophageal varices, and 4.3% had grade IV esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence has been reported to range from 11% to 98%. 62 However, bleeding is relatively less common, with 10.8% of patients having chronic bleeding and only 2.5% acute bleeding. 63 Platelet counts are lower in patients with PHG.…”
Section: Non-variceal Gastrointestinal Bleedingmentioning
confidence: 99%
“…The diagnostic accuracy of platelet count to spleen diameter ratio in 111 cirrhotic patients for sensitivity, specificity, PPV, NPV, and accuracy of PSR were 87.23%, 5.88%, 83.67%, 7.69%, and 74.7%, respectively. 62 The right liver lobe-diameter-to-albumin ratio and platelet-count-to-spleendiameter ratio are noninvasive predictors of the presence and severity of portal hypertensive gastropathy. 62 There are no reports on the impact of thrombocytopenia on bleeding from PHG.…”
Section: Non-variceal Gastrointestinal Bleedingmentioning
confidence: 99%
See 1 more Smart Citation